Intraoperative Spinal Cord Monitoring: Focusing on the Basic Knowledge of Orthopedic Spine Surgeon and Neurosurgeon as Members of a Team Performing Spine Surgery under Neuromonitoring - Tetsuya Tamaki (Spine Surgery and Related Research, 2021)
An intraoperative functional spinal cord monitoring system is a technology used by spine and spinal cord surgeons to perform a safe surgery and to gain further surgical proficiency. However, no existing clinical neurophysiological method used in the operating room can monitor all complex spinal cord functions. Therefore, by observing the activities of certain neural action potentials transferred via limited neural tissues, surgeons need to deductively estimate the function of the whole spinal cord. Thus, as the number of spinal cord functions that need to be observed increases, spinal cord monitoring can be more reliable. However, in some situations, critical decision-making is affected by the limited capability of these methods. Nevertheless, good teamwork enables sharing of seamless information within the team composed of a surgeon, anesthesiologist, monitoring technician and nurses greatly contributes to making quick and accurate decisions. The surgeon, who is the person in charge of the team, should communicate with multidisciplinary team members using common technical terms. For this reason, spine and spinal cord surgeons must have appropriate knowledge of the methods currently used, especially of their utility and limitations. To date, at least six electrophysiological methods are available for clinical utilization: three are used to monitor sensory-related tracts, and three are used to monitor motor-related spinal cord functions. If surgeons perform electrode setting, utilizing their expertise, then the range of available methods is broadened, and more meticulous intraoperative functional spinal cord monitoring can be carried out. Furthermore, if the team members share information effectively by utilizing a clinically feasible judicious checklist or tools, then spinal cord monitoring will be more reliable.